Stabilitas UMKM Terhadap Pemulihan Ekonomi Masyarakat Palembang Pasca Pandemi Covid 19 - Mikail, Kiki; Panorama, Maya; Otoman, Otoman (Unversitas Islam Madura, 2022)
The study applied the theory of economic development to solve the problems and challenges of the economic recovery the small and medium enterprise (SME) after covid 19. The policy of social distancing has certainly change the economic activities of the people of Palembang. As a result of this policy, the economic growth Palembang People slows down and decreases by around 3 percent in 2020. Therefore, dynamic policies and development are needed to respond economic proble post covid 19. The peak economic slowdown in Palembang generally is influenced by a number of factors, ranging from decline in household consumption, investment to exports. Form three components, household consumption have paleyd major role in suppressing the Palembang economy due to the covid 19 pandemic. Therefore, for economic revival post covid 19, the Palembang local government must strengthen public institutions and services and align a strategies provide clear signal for better and systematic transition. Reforming renewable energy and increasing local production and the small and medium enterprise (SME) will gradually increase the economic resilience of the private sector. Increasing adequacy in the early of the post covid 19 economic recovery is significantly to control ivestment and economic growth in Palembang